2019
DOI: 10.1371/journal.pone.0226290
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Cosmed K5 portable calorimeter

Abstract: PurposeThe purpose of this study was to assess the accuracy of the Cosmed K5 portable metabolic system dynamic mixing chamber (MC) and breath-by-breath (BxB) modes against the criterion Douglas bag (DB) method.MethodsFifteen participants (mean age±SD, 30.6±7.4 yrs) had their metabolic variables measured at rest and during cycling at 50, 100, 150, 200, and 250W. During each stage, participants were connected to the first respiratory gas collection method (randomized) for the first four minutes to reach steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Direct observation was used as the reference criterion for posture, and an indirect calorimeter (K5; COSMED, Rome, Italy) was used as the reference criterion for activity. The K5 has been shown to measure the energy expenditure of a given task reliably (Crouter et al, 2019). It was calibrated before each recording according to the manufacturer's recommendation (flowmeter, scrubber, and room air).…”
Section: Measurement Equipmentmentioning
confidence: 99%
“…Direct observation was used as the reference criterion for posture, and an indirect calorimeter (K5; COSMED, Rome, Italy) was used as the reference criterion for activity. The K5 has been shown to measure the energy expenditure of a given task reliably (Crouter et al, 2019). It was calibrated before each recording according to the manufacturer's recommendation (flowmeter, scrubber, and room air).…”
Section: Measurement Equipmentmentioning
confidence: 99%
“…Previous studies have determined the validity and the reliability of the K5. They showed that the K5′s measurements of metabolic parameters (pulmonary ventilation, oxygen consumption, and carbon dioxide production) were comparable to the measurements from the breath-by-breath method of the traditional metabolic cart (Vyntus CPX; Jaeger-CareFusion, Höchberg, Germany), the automated breathing metabolic simulator (VacuMed automated system; VacuMed, USA), and the Douglas Bag Method [ 42 , 43 , 44 ]. Additionally, a recent study reported very high intra- and inter-device reliability of the K5 in measuring pulmonary ventilation, oxygen consumption, and carbon dioxide production (r > 0.99) [ 44 ].…”
Section: Methodsmentioning
confidence: 96%
“…Indirect calorimetry is commonly used to calculate respiratory quotient (CO 2 production/O 2 uptake) and resting energy expenditure, as well as to determine caloric needs in research [ 39 , 40 , 41 ]. The K5, our criterion measure, is a portable indirect calorimetry system (174 × 111 × 64 mm and 900 g, including battery and O 2 sensor) that is worn on the back with a harness [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This K5 COSMED system has been shown to produce reliable metabolic measurements compared with a metabolic simulator and a Douglas Bag. 16,19 The first 2 minutes for each condition were discarded to obtain steady-state oxygen consumption (VO 2 ) and heart rate data. The last 30 seconds for each condition were also discarded to account for any timing issues and any altered behavior as the participant anticipated the end of the condition.…”
Section: Assessment Of Energy Costmentioning
confidence: 99%